Feasibility, acceptability, and perceived benefits of a creative arts intervention for elementary school children living with speech, language and communication disorders - Léger-Goodes, T.; Herba, C. M.; Moula, Z.; Mendrek, A.; Hurtubise, K.; Piché, J.; Gilbert, M.; Bernier, M.; Simons, K.; Bélanger, N.; Smith, J.; Malboeuf-Hurtubise, C. (Frontiers in Child and Adolescent Psychiatry, 2024)
Background Children with speech, language, and communication disorders require specialized support in response to their emotional expression challenges. Not only is such support key for their development, but it is also essential for their mental well-being. Art making emerges as a valuable tool for enabling these children to convey emotions both verbally and non-verbally, fostering a positive self-concept. School-based arts interventions have the potential to improve self-concept and emotional expression, and more generally, the quality of life. However, there is limited empirical evidence regarding the feasibility, acceptability, and perceived effectiveness of a manualized, school-based creative arts intervention for this specific group. Aim This study aimed to develop and evaluate the feasibility, acceptability, and perceived benefits of an art-based intervention for elementary school students with speech, language, and communication disorders, using qualitative methods to obtain diverse perspectives. Results The findings indicate that the intervention was feasible and well received, as reported by teachers, students, and facilitators. Participants also discussed potential positive outcomes, including emotional expression, emotional growth, and fulfilment of autonomy, competence, and relatedness needs. Students found the workshops conducive to sharing emotions and took pride in the creative process. Teachers gained deeper insights into their students, fostering positive classroom relationships. Observational data triangulated these findings. Conclusion This innovative project suggests that art-based interventions can potentially benefit students’ emotional expression, but further experimental studies are needed to substantiate these effects.